Unified viscoplasticity modelling and its application to fatigue-creep behaviour of gas turbine rotor. (February 2018) - Benaarbia, A.; Rae, Y.; Sun, W.
Highlights: An elasto-visco-plastic finite element modelling framework was developed including the associated UMAT codes. A 3D framework computational methodology following an implicit formulation and based on a radial return mapping algorithm was used. The methodology was applied to a classical industrial gas turbine rotor to study deformation mechanisms. The effects of thermal transients and geometry singularities on the development of residual stresses was discussed. Graphical abstract: Abstract: This paper presents an elasto-viscoplastic finite element modelling framework including the associated UMAT codes to investigate the high-temperature behaviour of a gas turbine rotor steel. The model used in the FE study is an improved and unified Chaboche–Lemaitre model which combines a power flow rule with non-linear anisothermal evolution of isotropic and kinematic hardening. The computational methodology is a three-dimensional framework following an implicit formulation and based on a radial return mapping algorithm. The UMAT is calibrated and validated across isothermal hold-time cyclic tests. The model is applied to a classical industrial gas turbine rotor to study the spatial heterogeneities and critical high stress areas within the rotor structure. The effect of thermal transients and geometry singularities on the development of residual stresses is underlined. Finally, the potential improvements and extensions of such FE viscoplastic analysis are discussed.